When the flathead mullet left St Lucia. Issue 2 (3rd April 2021) - Whitfield, AK
Abstract : The St Lucia estuarine system on the east coast of South Africa is a declared World Heritage Site and Ramsar Site of International Importance. A major ecological feature of St Lucia during the last century was the annual spawning migration of the flathead mullet Mugil cephalus down the system in the first half of each year. Top predators, such as the African fish eagle Haliaeetus vocifer, white pelican Pelecanus onocrotalus, Nile crocodile Crocodylus niloticus and Zambezi shark Carcharhinus leucas, have made extensive use of adult M. cephalus as a food resource. With the advent of prolonged closure of the St Lucia mouth in the first decade of the 21st century, caused by the lack of St Lucia system connectivity with the Mfolozi River and a prolonged drought, this spawning migration has ceased to exist. The almost complete disappearance of M. cephalus was reinforced in the second decade of this century by a continued lack of any estuarine–marine connectivity. This loss of connectivity between Lake St Lucia and the sea for more than 12 years is longer than the normal life cycle of M. cephalus, and the possibility exists that the putative subpopulation of this species that occupied the system prior to the turn of the century may have been rendered locally extinct. In January 2021, the berm at the mouth of the estuary was artificially breached and the outflow of St Lucia estuarine waters into the sea occurred for the first time since 2002. However, it remains to be seen whether the recovery of the M. cephalus population to pre-2000 levels will occur over the short term (year) or longer term (decade). It is strongly recommended that an adaptive management strategy, rather than a fixed management approach, be adopted for the sake of future connectivity of the St Lucia system to the marine environment.